Factors Related to Adolescent Girls' Attitudes Toward Consuming Rorano Herbal Medicine - Nurkila Suaib; Irawati Umaternate; Asmaryani Hasim (Journal of Science and Science Education, 2026)
This study comprehensively identified and analyzed multifaceted factors influencing adolescent girls' attitudes toward consuming Rorano herbal medicine within the Indonesian cultural context. This study aimed to analyze knowledge, interest, cultural, and economic factors related to adolescent girls' attitudes toward consuming Rorano Datang Bulan herbal medicine in the working area of ​​Bahari Berkesan Community Health Center, Ternate City. A cross-sectional, observational analytical design was implemented from July to December, using a structured questionnaire. All adolescent girls aged 12–16 years who were menstruating and consuming Rorano (n=65) were included through total sampling. The majority were aged 12–13 years (52.3%), had parental income below the minimum wage (UMR) (55.4%), and had knowledge and attitudes categorized as "adequate" (41.5% and 43.1%). Bivariate analysis showed that age was associated with knowledge (p=0.045; OR=1.80) and attitudes (p=0.032; OR=2.10). Interest was the strongest predictor of knowledge (p=0.001; OR=2.50) and attitude (p=0.005; OR=2.75), while culture was also significant (p≤0.020; OR≈1.90–2.00); economic variables were not significant. Logistic regression confirmed the interaction of interest×attitude (OR=2.87) and interest×knowledge (OR=2.55) as the main determinants. These findings indicate that strengthening interest and internalizing cultural norms can improve literacy and acceptance of herbal medicine in adolescents.